An Intrinsic Algorithm for Viewing Angle Tolerance of Object Discrimination in Human Subjects. - Jun-ya Okamura; Jin Oshima; Reona Yamaguchi; Wakayo Yamashita; Gang Wang (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2020)
Prevailing theories suggest that view-invariant object recognition is accomplished via spatiotemporal correlations of multiple views that bind different views to the same object. However, it is unknown how the exposure to multiple views without association affects view-invariant recognition generating. Behavioural studies have shown that monkeys acquired view-invariant object recognition capability in a range of the viewing angles of 30° to 60° after experiencing discrimination of similar objects at each of several viewing angles without associating different views, but the monkeys could not discriminate novel objects from similar distractors when the viewing angle changed. In the present study the development of the view invariance was tested in the human subjects and compared with the results of the monkeys previously reported. The view-invariant object recognition capability of human subjects was tested using either familiar objects that the subjects experienced in a preparatory object discrimination task at the same viewpoints or novel objects that the subjects had never experienced. In the viewing angle range of 30°, human subjects showed significant object discrimination capability across views, with no need for prior experience of the objects. Prior discrimination experience within the same viewpoints endowed the human subjects with broadening of the viewing angle tuning, because an object discrimination test immediately after the prior discrimination experience at a single view showed wider viewing angle tuning than a test without prior experience.